PERAN EKONOMI LINGKUNGAN DALAM PENGELOLAAN PERKEBUNAN SAWIT DI KABUPATEN TANAH LAUT - Dini Maulidda Aprilia; Rosalina Kumalati; Ellyn Normelani (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2024)
Oil palm plantations are a leading sector in the economy of Tanah Laut Regency, South Kalimantan. However, despite their contribution to regional income and community welfare, these activities also cause environmental problems such as deforestation, land degradation, and water pollution. This study aims to analyze the role of environmental economics in supporting sustainable oil palm plantation management in Tanah Laut Regency. The research method uses a qualitative descriptive approach with data collection through literature studies, field observations, and interviews with stakeholders. The results show that the application of environmental economic principles, such as the economic valuation of natural resources, environmental incentive policies, and sustainable plantation practices, can provide long-term economic benefits while maintaining ecosystem sustainability. This study emphasizes the importance of collaboration between the government, companies, and communities in implementing environmental economic principles to achieve a balance between economic growth and environmental sustainability